2016
DOI: 10.1177/1524839916631537
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Patient Exposure to a Video-Based Intervention in STD Clinic Waiting Rooms

Abstract: Safe in the City , a video intervention for clinic waiting rooms, was previously shown to reduce sexually transmitted disease (STD) incidence. However, little is known about patients’ recall of exposure to the intervention. Using data from a nested study of patients attending clinics during the trial, we assessed whether participants recalled Safe in the City, and, if so, how the intervention affected subsequent attitudes and behaviors. Analyses were restricted to responses to a 3-month follow-up questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Overall, these findings reinforce emerging literature promoting the use of video interventions in healthcare. Video interventions have been used successfully in sexually transmitted disease clinics [ 53 , 54 , 55 , 56 ], palliative care clinics [ 57 ], for home visits by community health workers [ 58 ], and in both prenatal and HIV posttest counseling [ 59 , 60 ]. As in these studies, our study suggests that the VITAL Start intervention is acceptable, feasible, and impactful, as the majority of the women reported positive behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, these findings reinforce emerging literature promoting the use of video interventions in healthcare. Video interventions have been used successfully in sexually transmitted disease clinics [ 53 , 54 , 55 , 56 ], palliative care clinics [ 57 ], for home visits by community health workers [ 58 ], and in both prenatal and HIV posttest counseling [ 59 , 60 ]. As in these studies, our study suggests that the VITAL Start intervention is acceptable, feasible, and impactful, as the majority of the women reported positive behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that dramatized video increases viewer identification with characters, thus driving narrative engagement and the creation of episodic memories - which improves memory recall. A study evaluating video interventions in clinic waiting rooms supports this pathway, finding excellent recall and retention of the video's content at 3-month follow up 15 . Further, narratives are intrinsically persuasive, potentially offering a medium to communicate scientific information to non-expert audiences, such as children 16 Videos have been used to teach the fundamentals of the immune system through analogies such as a castle invasion theme 17 .…”
Section: Digital Opportunitiesmentioning
confidence: 99%
“…A study evaluating video interventions in clinic waiting rooms supports this pathway, finding excellent recall and retention of the video's content at 3-month follow up. 15 Further, narratives are intrinsically persuasive, potentially offering a medium to communicate scientific information to non-expert audiences, such as children 16 Videos have been used to teach the fundamentals of the immune system through analogies such as a castle invasion theme. 17 Many may remember the episode of The Magic School Bus on the immune system, where Ms. Frizzle and her class shrink and slip into Ralphie's veins to see what is making him sick.…”
Section: Digital Opportunitiesmentioning
confidence: 99%
“…To be compelling, educational videos must be culture-specific so as to align with local cultural beliefs, life experiences and socioeconomic factors (Brevik et al, 2020) because ‘culture-centred design and development’ leads to meaningful learning experiences and better learning outcomes. In addition, videos are effective in increasing knowledge retention among viewers (Besera et al, 2016; Tuong et al, 2014). It is important, however, for educational videos aimed at encouraging dietary changes among hypertension patients to be both dependable and authenticated.…”
Section: Introductionmentioning
confidence: 99%